Stability analysis of power system including facts (TCSC) effects by direct method approach - Colvara, Laurence Duarte [UNESP]; Araujo, Silvio Cesar Braz [UNESP]; Festraits, Ednilton Bressan [UNESP] (Elsevier, 2005)
The problem of power system stability including the effects of a flexible alternating current transmission system (FACTS) is approached. First, the controlled series compensation is considered in the machine against infinite bar system and its effects are taken into account by means of construction of a Lyapunov function (LF). This simple system is helpful in order to understand the form the device affects dynamic and transient performance of the power system. After, the multimachine case is considered and it is shown that the single-machine results apply to multimachine systems. An energy-form Lyapunov function is derived for the power system including the FACTS device and it is used to analyse damping and synchronizing effects due to the FACTS device in single-machine as well as in multimachine power systems. © 2005 Elsevier Ltd. All rights reserved.
Keywords: CSC; Direct methods; Energy function; FACTS; Power system stability; Damping; Electric currents; Electric potential; Electric power transmission; Functions; Lyapunov methods; Mathematical models; Oscillations; Resonance; Synchronization; System stability; Controllable series compensator (CSC); Energy functions; Flexible alternating current transmission system (FACTS); Electric power systems